THE UTILIZATION OF KAUM-BASED VILLAGE FUNDS AS A FORM OF STRENGTHENING THE CAPACITY OF THE NAGARI GOVERNMENT DURING THE COVID-19 PANDEMIC - Safitri, Cici; Valentina, Tengku Rika; Putera, Roni Ekha (Sosiohumaniora, 2024)
This study discusses the capacity of the nagari government to utilize village funds during the COVID-19 pandemic. Limitations in communication patterns, interaction, and community legitimacy are identified as issues in policy implementation. As the front line to accelerate economic recovery for the community during the pandemic, the nagari government has to offer various innovations in policy implementation, including the utilization of village funds. Remarkably, one of the nagari in West Sumatra, namely Nagari Pasia Laweh, utilized the pandemic as a turning point for generating various innovations using village funds. Consequently, this nagari was rewarded as the best Nagari in village fund transparency in 2020 and the best nagari in West Sumatra in 2021. This study employed a qualitative method to observe the phenomena related to the institutional capacity of nagari in the utilization of village funds during the pandemic. The data were collected through in-depth interviews with the purposive sampling technique. The results indicate that various policy innovations are carried out through schemes involving local actors in Nagari Pasia Laweh using a kaum-based method. The collaboration between the government and local elite facilitates the acceptance and implementation of various policies in the community. Thus, community participation and legitimacy greatly influence Nagari Pasia Laweh to the extent that it is selected as the best nagari.